KONSTRUKSI PEMAHAMAN MAKNA JIHAD PADA MASYARAKAT LANTO JAYA - Syukran Zikrullah; Muhammad Syarif Hasyim (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2022)
Different in interpreting the meaning of jihad, there are those who understand jihad by fighting evil and there are also those who interpret jihad by increasing the quality of faith in Allah SWT, or jihad against lust. Through this research it is hoped that it can contribute ideas to the Lanto Jaya village community so that differences among the community do not cause divisions, but with differences this thesis departs from a problem of how the Lanto Jaya village community understands the meaning or meaning of jihad and how to implement jihad in the daily life of the people of Lanto Jaya. The results of this study indicate that the understanding of jihad in the Lanto Jaya village community does have differences. The schools that develop in society are the Shafi'i school, the Hanbali school and the Maliki school. However, what is of concern in this village is that there are still frequent differences of opinion that depart from these different understandings. Jihad in the village of Lanto Jaya is closely related to the impact of the incident in 2000 which involved two religions namely Islam and Christianity, as a result of this incident many people immediately understood jihad. There are many understandings or groups that enter the midst of society and provide an understanding of jihad. Due to the lack of knowledge about religion at that time, the community actually made people more familiar with one another.